Structural selection of a native fold by peptide recognition. Insights into the thioredoxin folding mechanism - Santos, Javier (2009)
Thioredoxins (TRXs) are monomeric alpha/beta proteins with a fold characterized by a central twisted beta-sheet surrounded by alpha-helical elements. The interaction of the C-terminal alpha-helix 5 of TRX against the remainder of the protein involves a close packing of hydrophobic surfaces, offering the opportunity of studying a fine-tuned molecular recognition phenomenon with long-range consequences on the acquisition of tertiary structure. In this work, we focus on the significance of interactions involving residues L94, L99, E101, F102, L103 and L107 on the formation of the noncovalent complex between reduced TRX1-93 and TRX94-108. The conformational status of the system was assessed experimentally by circular dichroism, intrinsic fluorescence emission and enzymic activity; and theoretically by molecular dynamics simulations (MDS). Alterations in tertiary structure of the complexes, resulting as a consequence of site specific mutation, were also examined. To distinguish the effect of alanine scanning mutagenesis on secondary structure stability, the intrinsic helix-forming ability of the mutant peptides was monitored experimentally by far-UV CD spectroscopy upon the addition of 2,2,2-trifluoroethanol, and also theoretically by Monte Carlo conformational search and MDS. This evidence suggests a key role of residues L99, F102 and L103 on the stabilization of the secondary structure of alpha-helix 5, and on the acquisition of tertiary structure upon complex formation. We hypothesize that the transition between a partially folded and a native-like conformation of reduced TRX1-93 would fundamentally depend on the consolidation of a cooperative tertiary unit based on the interaction between alpha-helix 3 and alpha-helix 5